Decomposing the Rationale of Code Commits: The Software Developer’s Perspective. - Al Safwan, Khadijah; Servant-Cortés, Francisco Javier (Association for Computing Machinery (ACM), 2019)
Communicating the rationale behind decisions is essential for the success of software engineering projects. In particular, understanding the rationale of code commits is an important and often difficult task. We posit that part of such difficulty lies in rationale often being treated as a single piece of information. In this paper, we set to discover the breakdown of components in which developers decompose the rationale of code commits in the context of software maintenance, and to understand their experience with it and with its individual components. For this goal, we apply a mixed-methods approach, interviewing 20 software developers to ask them how they decompose rationale, and surveying an additional 24 developers to understand their experiences needing, finding, and recording those components. We found that developers decompose the rationale of code commits into 15 components, each of which is differently needed, found, and recorded. These components are: goal, need, benefits, constraints, alternatives, selected alternative, dependencies, committer, time, location, modifications, explanation of modifications, validation, maturity stage, and side effects. Our findings provide multiple implications. Educators can now disseminate the multiple dimensions and importance of the rationale of code commits. For practitioners, our decomposition of rationale defines a “common vocabulary” to use when discussing rationale of code commits, which we expect to strengthen the quality of their rationale sharing and documentation process. For researchers, our findings enable techniques for automatically assessing, improving, and generating rationale of code commits to specifically target the components that developers need.
https://www.acm.org/publications/openaccess#h-green-open-access
Correo 25/10/24
Keywords: Ingeniería del software; Soporte lógico - Mantenimiento; Software maintenance; Software evolution; Program comprehension